Design and Optimum of Dust Collector with Corrugated Plate for Underground Mine - Ming Li; Chao Wu; Zhi-yong Zhou; Wei-chun Lian; Zhi-xiong Chen (Advances in Civil Engineering)
A set of dust collectors was designed with corrugated plate for an underground metal mine, which has low ventilation resistance, simple maintenance, and strong environmental adaptability. A three-dimensional simulation model was built based on ANSYS-Fluent software, and it was used to analyze the influence law of key parameters on the comprehensive dust removal efficiency; the angle of corrugated plate to the horizontal plane, the surface characteristics of plate, pressure loss and dust removal efficiency were discussed. The optimal design scheme of the dust collector was determined according to the simulation results. The dust collection was carried out in the Fankou lead-zinc underground metal mine in China, and the total dust removal efficiency was more than 95%, and for respiratory dust, it was more than 85%. This dust collector can be widely used in similar underground metal mines.